Réponses

  • Utilisateur Brainly
2014-03-27T19:19:28+01:00
On pose x= \frac{ \sqrt{5}+1 }{2}
alors x^2= \frac{1}{4}( \sqrt{5} +1)^2= \frac{1}{4}(5+2 \sqrt{5}+1)= \frac{3}{2} + \frac{ \sqrt{5} }{2}
donc x^2-x-1= \frac{3}{2} + \frac{ \sqrt{5} }{2} - \frac{ \sqrt{5} }{2}- \frac{1}{2}-1=0

ceci est normal puisque cette solution s'appelle : "le nombre d'or"
  • Utilisateur Brainly
2014-03-27T19:25:13+01:00
(5+2V5+1)/4 - (V5+1)/2 - 1 = 


(5+2V5+1)/4 - (2V5+2)/4 - 4/4 =

(5+2V5+1-2V5-2-4)/4 = ..............